2003
DOI: 10.1029/2002jd003200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of biomass and biofuel emissions to trace gas distributions in Asia during the TRACE‐P experiment

Abstract: [1] A comprehensive emission inventory with enhanced spatial and temporal resolution is used to help quantify the contribution from three source categories (fossil, biofuel, and biomass burning) during the NASA TRACE-P experiment. Daily biomass burning emissions are developed to support this analysis. Emissions of 27 species and their ratios, by sector, region, and source category are presented. The emission distributions and chemical composition are further analyzed using various statistical techniques. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 32 publications
2
102
0
1
Order By: Relevance
“…Fossil fuel burning was reported to be an important contributor across large areas of the Asian continent, especially in the fast developing regions of China and Southeast Asia (Russo et al, 2003;Woo et al, 2003). In East Asia, transport from South Korea and Japan is also depicted in the regional emissions Carmichael et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fossil fuel burning was reported to be an important contributor across large areas of the Asian continent, especially in the fast developing regions of China and Southeast Asia (Russo et al, 2003;Woo et al, 2003). In East Asia, transport from South Korea and Japan is also depicted in the regional emissions Carmichael et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the mentioned satellite fire map, higher contributions of biomass burning in this case would be expected. Woo et al (2003) reported that biofuel emissions were more strongly correlated with fossil fuel emissions than biomass burning. Here the correlation between CH 3 Cl and C 2 Cl 4 is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The following sections explain how we modeled each of these processes. We modeled the aerosol dynamics within the plume with the Particle Monte Carlo (PartMC) model (Riemer et al, 2009) coupled to the Model for Simulating Aerosol Interactions and Chemistry (MOSAIC) (Zaveri et al, 2008). PartMC-MOSAIC is a box model that tracks the composition of individual particles within a Lagrangian air parcel as they evolve due to Brownian coagulation, condensation and evaporation (i.e., gas-particle partitioning), chemical reactions, and dilution.…”
Section: Methodsmentioning
confidence: 99%
“…PartMC-MOSAIC is a box model that tracks the composition of individual particles within a Lagrangian air parcel as they evolve due to Brownian coagulation, condensation and evaporation (i.e., gas-particle partitioning), chemical reactions, and dilution. Whereas coagulation and dilution are modeled as stochastic processes with a Poisson distribution, MOSAIC simulates the gas and particle-phase thermodynamics, and gas-particle mass transfer (Riemer et al, 2009;Zaveri et al, 2008). MOSAIC uses the SORGAM scheme to model the formation of low-volatility and semi-volatile products from the oxidation of precursors, and their gas-particle partitioning (Schell et al, 2001;Zaveri et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…These include the Asian Pacific Regional Aerosol Characterization Experiment (ACE-Asia) (Anderson et al, 2003;Conant et al, 2003;Arimoto et al, 2006;Sullivan et al, 2007), the East Asian Study of Tropospheric Aerosols: an International Regional Experiment (EAST-AIRE) (Anderson et al, 2003;Huebert et al, 2003;Zhang et al, 2003b;Arimoto et al, 2004;Kim et al, 2005;, the Transport and Chemical Evolution over the Pacific (TRACE-P) aircraft mission (Jacob et al, 2003;Tu et al, 2003;Woo et al, 2003;Allen et al, 2004;Mari et al, 2004), the Intercontinental Chemical Transport Experiment-Phase B (INTEX-B) campaign (McKendry et al, 2008;Zhang et al, 2009), and the Pacific Dust Experiment (PACDEX) (Huang et al, 2008a). Although there has been much progress in measuring the physical and optical properties of dust and non-dust aerosols (Cao et al, 2014;Jing et al, 2015), the monthly and seasonal variations in these aerosols have yet to be well quantified, especially across the Loess Plateau, near the dust sources.…”
Section: Introductionmentioning
confidence: 99%